Beyond speed and strategy: A configurational analysis of collective attention to post-match institutional discourse in the UEFA Champions League - Zhichen Ling; Xinlei Ren; Bingquan Luo (PLoS ONE, 2026)
Post-match institutional communication has become a visible component of elite football events, yet comparable official messages can receive very different levels of public attention. This study examines UEFA Champions League post-match communication as a configurational problem rather than as a linear consequence of response speed or message strategy. Using 25 theoretically selected focal club-event observations from the 2017–2018–2022–2023 seasons, it calibrates one outcome set, High_News, from a Raw_Mentions-derived media-visibility proxy and four causal-condition sets: High_Delay, High_Shock, High_Stakes, and High_TemplateDeviation. The analysis uses conservative coding of template deviation, separating response latency from communication form. The intermediate solution identifies one stable high-stakes legacy pathway and one sensitivity-dependent crisis-minimalism pathway. The stable pathway combines non-delayed response, low outcome shock, high match stakes, and trophy/legacy-oriented template deviation. The crisis-minimalism pathway is retained in the baseline solution but is interpreted cautiously because it depends on medium-confidence coding and changes under strict recoding. The analysis of ~High_News confirms causal asymmetry: non-membership in the high-attention set is not simply the inverse of the pathway(s) associated with High_News. The findings contribute to sport communication research by showing how event structure and institutional discourse combine to produce bounded media visibility, while avoiding population-level claims about all football matches or internal platform algorithms.